Endothelial dysfunction and systemic inflammation in persons with echolucent carotid plaques - Notø, Ann-Trude With; Mathiesen, Ellisiv Bøgeberg; Amiral, Jean; Vissac, Anne Marie; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2006)
Echolucent carotid plaques are associated with high risk for future ischemic cerebrovascular events independent of the degree of stenosis. Elevated levels of markers of systemic inflammation and endothelial dysfunction are predictors for future myocardial infarction and stroke.The present study was undertaken to investigate the relations between plaque morphology, endothelial dysfunction assessed by tissue-plasminogen activator antigen (t-PA ag) and von Willebrand factor (vWF), and systemic inflammation in persons with carotid stenosis.We conducteda crosssectional study including 133 persons with carotid stenosis and 138 controls without stenosis recruited from the populationbased Tromsø Study. High-resolution B-mode and colour Doppler/pulsed-wave Doppler ultrasonography of both carotid arteries was performed, and plaque morphology in terms of echogenicity was assessed. Persons with carotid stenosis had significantly higher plasma t-PA and vWF concentrations than controls. There was a significant inverse relationship between t-PA ag and plaque echogenicity (p=0.034).The increased plasma t-PA ag in persons with carotid stenosis was not associated with increased plasminogen activator inhibitor-I (PAI-1).Persons with echolucent carotid plaques had higher degree of systemic inflammation, and plasma t-PA and vWF concentration increased significantly across quartiles of WBC, fibrinogen, and hs-CRP. Our findings may suggest that plasma t-PA may be superior to vWF asa marker for endothelial dysfunction due to its ability to discriminate between various plaque echogenicity, and that the predictive role of t-PA ag in cardiovascular disease is independent of inhibited fibrinolysis.
Keywords: Atherosclerosis; ultrasound / diagnosis; von Willebrand factor; plasminogen activators; cerebrovascular disease